Pengaruh Slice Thickness terhadap Signal to Noise Ratio (SNR) dari Hasil Penyinaran CT Scan di RSUP Prof. Dr. I.G.N.G Ngoerah - Kusumaningsih, Lusi Putu Russita; Suryatika, I Bagus Made; Trisnawati, Ni Luh Putu; Irhas, Rozi (Universitas Hamzanwadi, 2023)
A research has been carried out on the effect of slice thickness on SNR values from the results of CT Scan irradiation at Prof. Dr. I.G.N.G Ngoerah Hospital. Variations in the thickness of the slices used are 1 mm, 3 mm, 5 mm, and 7 mm. The tube voltage, tube current, and FOV used are constant, namely 120 kV, 200 mA, and 380 mm. SNR value analysis was calculated using the average object value and SD background for each material. Based on the results of a simple linear regression test, the thickness of the slices obtained has an effect of 99.9% on the SNR value. These results indicate that the greater the thickness of the slice used, so the SNR value will increasesas the SNR value increases, it will improve image quality.